PEMANFAATAN MEDIA SOSIAL SEBAGAI SARANA PROMOSI KAMPUNG WISATA BATIK KEDUNGGUDEL DI KABUPATEN SUKOHARJO - Gama, Betty; Saputro, Ardean Rio; Hariyanto (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2025)
Social media provides many benefits to its users. A variety of information is available. One of them is tourist information about Kedunggudel Batik Village in Kenep Village, Sukoharjo Regency. There are several batik artisans, but the ones that still exist today are Batik Ayu Kusuma and Batik Satrio Utomo. Both use Instagram as a promotional medium for their products. The owners of both batik makers are not very skilled in using Instagram. As a result, their batik production are less well-known, and as a result, their high-quality batik with beautiful patterns receives less attention from the public and netizens. Batik Ayu Kusuma and Batik Satrio Utomo do not use influencers or Instagram celebrities as promotional media for their batik. The purpose of this study was to determine how Batik Ayu Kusuma and Batik Satrio Utomo utilize social media as a promotional tool and the obstacles they face in conducting promotions. This study used qualitative research methods. Data analysis used qualitative analysis. Data sources include primary and secondary data. The analysis method uses the Miles and Hubermas model. The results of the study show that the use of Instagram could increase tourist visits to Kedunggudel Batik Village, while the obstacles that occur were not utilizing Instagram social media optimally, not using influencers or Instagram celebrities to promote batik and batik motifs based on local image.